1996
DOI: 10.1111/j.1651-2227.1996.tb14215.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy development and macromolecular absorption in infants with different feeding regimens during the first three days of life. A three‐year prospective follow‐up

Abstract: A group of 129 infants were randomly assigned at birth to one of three feeding regimens: human milk (HM), cow's milk formula (CMF) or a casein hydrolysate formula (CHF) during the first 3 days of life. Blood samples were taken on at 4 days and at 2, 4, 8, 12 and 24 months of age. Macromolecular absorption was analysed by measuring the serum concentration of human alpha-lactalbumin (S-alpha-LA) with a competitive radioimmunoassay (RIA). Total serum IgE was measured by RIA. A family history of allergy correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…ivas ociated \vith a significantly lower incidence of ;illergy than >tarvation during the tirst da)s of life ( 2 7 ) : these finding5 are not supported by StintLins and ZetterstrCim ( 2 6 ) and J~ivoiieti ct al. (28).…”
Section: Holi ~J I (mentioning
confidence: 99%
See 1 more Smart Citation
“…ivas ociated \vith a significantly lower incidence of ;illergy than >tarvation during the tirst da)s of life ( 2 7 ) : these finding5 are not supported by StintLins and ZetterstrCim ( 2 6 ) and J~ivoiieti ct al. (28).…”
Section: Holi ~J I (mentioning
confidence: 99%
“…Allergy during childhood was reported of comparable incidence in children fed human milk, soy or cow's milk (53). Breastfeeding has nlo effect on the incidence of eczema (36), atopic disease or increase in IgE (28,54). A study in the Munich region on 6535 children concluded that breastfeeding alone had no long-term protective effect on atopic disease (55).…”
Section: Studies Suggesting Breastfeeding Has No Preventive Effect Onmentioning
confidence: 99%
“…Another study13 showed a protective effect of breast feeding on atopy only when the age of the infant when other milk was introduced was considered 14. Several studies have, however, failed to show an association between breast feeding and either asthma or atopy 1517. Halpern et al17 reported childhood allergy to be equally common in children fed human, soy, or cows' milk.…”
Section: Introductionmentioning
confidence: 99%
“…However, using the criteria of a 2006 Cochrane review, 41 only 14 randomized or quasirandomized (eg, using alternation) trials in term infants compared the use of partially or extensively hydrolyzed formula with the use of human milk or an adapted cow milk formula. [42][43][44][45][46][47][48][49][50][51][52][53][54][55] All of these trials have followed up with at least 80% of study participants. It is important to note that none of these studies reported any adverse effects, including any adverse effect on infant growth.…”
Section: Role Of Hydrolyzed Formula On the Development Of Atopic Diseasementioning
confidence: 99%